Ocular and Mucocutaneous Sequelae among Survivors of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis in Togo - Bayaki Saka; Abla Séfako Akakpo; Julienne Noude Teclessou; Garba Mahamadou; Abas Mouhari-Toure; Kossi Dzidzinyo; Adam Nouhou Diori; Nidain Maneh; Sabin Prince-Agbodjan; Koussake Kombaté; Komi Balo; Kissem Tchangai-Walla; et al. (Dermatology Research and Practice)
Aim. The aim of this study was to assess ocular and mucocutaneous sequelae among SJS/TEN survivors and identify risk factors of ocular sequelae. Patients and Method. Late complications among SJS/TEN survivors were assessed using 2 methods: a retrospective assessment of medical records only or a retrospective assessment of medical records and physical examination of survivors who were contacted by phone. Results. Between January 1995 and December 2017, 177 cases of SJS/TEN (138 cases of SJS, 29 cases of TEN, and 10 cases SJS/TEN overlap) were admitted into two university hospitals of Lomé (Togo). There were 113 women and 64 men, with an average age of 31.7±13.0 years (range: 5 to 80 years). The most used drugs were antibacterial sulfonamides (35.6%) and nevirapine (24.3%). HIV serology was positive in 68 (59.1%) of the 115 patients tested. Sixty-four (52,5%) of the 122 patients, who had been examined by an ophthalmologist during the acute stage, had acute ocular involvement, which was mild in 27.9% of patients, moderate in 13.1%, and severe in 11.5%. We recorded 17 deaths (i.e., three cases of SJS, 12 of TEN, and two of SJS/TEN overlap), including 11 cases of HIV infected patients. Of the 160 SJS/TEN survivors, only 71 patients were assessed 6 months after hospital discharge. Among them, forty-three (60.6%) patients had sequelae. Concerning mucocutaneous sequelae, the main lesions were diffuse dyschromic macules (38.0% of patients) and ocular sequelae were dominated by decreased visual acuity (14.1% of patients). In multivariate analysis, exposure to sulfadoxine (odds adjusted ratio = 5.95; 95%CI= [1.36-31.35]) and moderate (adjusted odds ratio = 5.85; 95%CI = [1.23-31.81]) or severe (adjusted odds ratio = 48.30; 95%CI = [6.25-1063.66]) ocular involvement at acute stage were associated with ocular sequelae. Conclusion. Ocular and mucocutaneous sequelae are common in SJS/TEN survivors. Exposure to sulfadoxine and severity of acute ocular involvement are risk factors of ocular sequelae.